Hortaea werneckii isolates exhibit different pathogenic potential in the invertebrate infection model Galleria mellonella - Anthonies, Stephanie; Vargas-Muñiz, José M. (Frontiers in Fungal Biology, 2022)
Hortaea werneckii is a black yeast with a remarkable tolerance to salt. Most studies have been dedicated to understanding how H. werneckii adapts to hypersaline environments. H. werneckii has an unconventional cell cycle in which it alternates between fission and budding, which is modulated by cell density. Additionally, H. werneckii can cause superficial mycosis of the palm and sole of humans. Here, we determine the impact of salt concentration on the EXF-2000 strain’s cell division pattern and morphology by performing timelapse microscopy at different salt concentrations. At low density and no salt, EXF-2000 primarily grows as pseudohyphae dividing mainly by septation. When grown in the presence of salt at a similar concentration to saltwater or hypersaline environments, we observe it grows first by undergoing fission followed by budding at the poles. Then, we examined a collection of 16 isolates in the presence of 0.6M NaCl, including isolates from marine and hypersaline environments and isolates from patients. These isolates exhibit a wide diversity in colony shape and cellular morphology. The isolates grew as yeast, pseudohyphae, and true hyphae, indicating that isolates can exhibit various cell morphologies under similar environmental conditions. We used the insect larvae Galleria mellonella to determine the pathogenic potential of our isolates. We observe that only a subset of isolates can cause death in our model, and there was no correlation between H. werneckii morphology and capacity to cause disease. Taken together, H. werneckii genomic and phenotypic diversity can serve as a model to better understand how phenotypes and pathogenic potential evolve in environmental fungi.